The Melting Layer: A Laboratory Investigation of Ice Particle Melt and Evaporation near 0°C - (:unkn) unknown (My University, 2005)
Abstract Melting, freezing, and evaporation of individual and aggregates of snow crystals are simulated in the laboratory under controlled temperature, relative humidity, and air velocity. Crystals of selected habit are grown on a vertical filament and subsequently melted or evaporated in reverse flow, with the velocity adjusted for appropriate fall speed to reproduce conditions of the melting layer. Nonequilibrium conditions are simulated for larger melting ice particles surrounded by smaller drops at a temperature up to +5°C or growth of an ice crystal surrounded by freezing ice particles down to −5°C. Initial melting of well-defined faceted crystals, as individuals or in combination, occurs as a water layer >10 μm thick. For larger (>100 μm) crystals the water becomes sequestered by capillary forces as individual drops separated by water-free ice regions, often having quasiperiodic locations along needles, columns, or arms from evaporating dendrites. Drops are also located at intersections of aggregate crystals and dendrite branches, being responsible for the maximum of the radar scatter. The drops have a finite water–ice contact angle of 37°–80°, depending on ambient conditions. Capillary forces move water from high-curvature to low-curvature regions as melting continues. Toward the end of the melting process, the ice separating the drops becomes sufficiently thin to fracture under aerodynamic forces, and mixed-phase particles are shed. Otherwise ice-free drops are shed. The melting region and the mechanism for lowering the melting layer with an increasing precipitation rate are associated with smaller ice particle production capable of being lofted in weaker updrafts.
The Melting Layer